White Supremacy: America's Original Sin? - Papa Malick BA (The Journal of Studies in Language, Culture and Society)
Writing about white supremacy in the US may sound unoriginal and trite but I believe it is way too important to continue studying it with regard to its relevancy and the challenges it continues to pause to justice, equity and harmony in the American society. Undoubtedly, it is path breaking to say that it is America’s original sin even though we have long been made to believe that racism is America’s original sin. Ideology and force have been its main vehicles. In other words, racism, or rather racialism, and violence allowed it to become institutionalized and to subtly operate. Power and privileges are at its heart and it seeks their accumulation and control. That is why it is the most decried and biggest internal problem of the nation. In the face of deeper divide of the US national fabric, regular discriminatory practices and hate acts against African-Americans that often culminate to countless murders and what seems like hereditary poverty, it becomes more than relevant to tackle the problem and find it solutions. Thus, this paper intends to study how white supremacy has become the nation’s original sin, its characteristics, the ways in which it operates and its consequences on African-Americans particularly. It contends that it has established and rooted itself in the nation’s fabric since settler colonialism in the America’s in the 15th century. It has been consolidated and institutionalized through nation-building and maintained itself through astute resilience. At the end, this capacity to adapt itself and continue to exist despite serious challenges makes it hard to be routed.